Proposal of Standardization to Assess Adherence With Medication Records: Methodology Matters. (May 2016) - Arnet, Isabelle; Kooij, Marcel J.; Messerli, Markus; Hersberger, Kurt E.; Heerdink, Eibert R.; Bouvy, Marcel
Background: Medication adherence is the process by which patients take their medication as prescribed and is an umbrella term that encompasses all aspects of medication use patterns. Ambiguous terminology has emerged to describe a deviation from prescribed regimen, forcing the European ABC Project to define 3 phases of medication use: initiation, implementation, and discontinuation. However, different measures of medication adherence using medication records are currently available that do not always distinguish between these phases. The literature is lacking standardization and operationalization of the assessment methods.Objective: To propose a harmonization of standards as well as definitions of distinct measures and their operationalization to quantify adherence to medication from medication records.Methods: Group discussions and consensus process among all coauthors. The propositions were generated using the authors' experiences and views in the field of adherence, informed by theory.Results: The concepts of adherence measures within the new taxonomy were harmonized, and the standards necessary for the operationalization of adherence measures from medication records are proposed. Besides percentages and time-to values, the addition of a dichotomous value for the reinitiation of treatment is proposed. Methodological issues are listed that should be disclosed in studies on adherence.Conclusions: The possible impact of the measures in adherence research is discussed. By doing this, the results of future adherence research should gain in accuracy. Finally, studies will become more transparent, enabling comparison between studies.